The crucible / - Miller, Arthur,,Dreyfuss, Richard,,Keach, Stacy (Bloomsbury, 2015)
Arthur Miller's classic parable of mass hysteria draws a chilling parable between the Salem witch hunt of 1692 and the McCarthyism which gripped America in the 1950s.
10.5040/9781580814355.01
Keywords: Witchcraft; Radio plays; American.; Audiobooks.